Case study : demise of Brent crude oil futures contract on SGX. - Ng, Choon Cheong. (2008)
This paper seeks to determine reasons that led to the demise of the Brent Crude Oil Futures Contract listed on SGX. Specifically, we examine the market microstructure: the number of trades, trading volume, open interest, bid-ask spread and volatility. In addition, we examine the mutual offset feature of the contract that allows simultaneous trading on both SGX and International Commodity Exchange (ICE) to determine whether such a feature affects the market microstructure. By examining the reasons that led to its failure, we hope to establish the drivers of successful contracts. This can be useful to SGX when they design contracts in future so as to maximize their chances of success. Our study shows that our hypothesis with regards to the mean volume, open interest and number of trades show a decline as the futures contract nears its demise holds. Similarly, the bid-ask spread of the futures contract widens too. Investigations of the mutual offset feature of Brent Crude Oil futures contract between SGX and ICE provides positive evidence that trading volume, open interest and number of trades increases significantly during the period 2 (1600-1745) when mutual offset is available. However the period 3 (1802-0413) proves otherwise.